Neuropathic pain phenotyping as a predictor of treatment response in painful diabetic neuropathy: Data from the randomized, double-blind, COMBO-DN study - Bouhassira, Didier; Wilhelm, Stefan; Schacht, Alexander; Perrot, Serge; Kosek, Eva; Cruccu, Giorgio; Freynhagen, Rainer; Tesfaye, Solomon; Lledó, Alberto; Choy, Ernest; Marchettini, Paolo; Micó, Juan Antonio; et al. (Pain (Amsterdam), 2014)
Duloxetine and pregabalin have different effects on neuropathic pain components. This might explain differential responses to these drugs when given either alone or in combination. Sensory profiles are heterogeneous in neuropathic pain disorders, and subgroups of patients respond differently to treatment. To further explore this, patients in the COMBO-DN study were prospectively assessed by the Neuropathic Pain Symptom Inventory (NPSI) at baseline, after initial 8-week therapy with either duloxetine or pregabalin, and after subsequent 8-week combination/high-dose therapy. Exploratory post hoc cluster analyses were performed to identify and characterize potential subgroups through their scores in the NPSI items. In patients not responding to initial 60mg/d duloxetine, adding 300mg/d pregabalin for combination treatment was particularly effective regarding the dimensions pressing pain and evoked pain, whereas maximizing the duloxetine dose to 120mg/d appeared more beneficial regarding paresthesia/dysesthesia. In contrast, adding 60mg/d duloxetine to 300mg/d pregabalin in case of nonresponse to initial pregabalin led to numerically higher decreases in all NPSI dimensions/items compared to maximizing the pregabalin dose to 600mg/d. Cluster analysis revealed 3 patient clusters (defined by baseline scores for the 10 NPSI sensory items) with different pain profiles, not only in terms of overall pain severity, but also across NPSI items. Mean Brief Pain Inventory average pain improved in all clusters during combination/high-dose therapy. However, in patients with severe pain, the treatment effect showed a trend in favor of high-dose monotherapy, whereas combination therapy appeared to be more beneficial in patients with moderate and mild pain (not significant). These complementary exploratory analyses further endorse the idea that sensory phenotyping might lead to a more stratified treatment and potentially to personalized pain therapy.